2004
DOI: 10.1038/sj.bjp.0705665
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline inhibits pacemaker currents through stimulation of β1‐adrenoceptors in cultured interstitial cells of Cajal from murine small intestine

Abstract: 1 Interstitial cells of Cajal (ICCs) are pacemaker cells that activate the periodic spontaneous inward currents (pacemaker currents) responsible for the production of slow waves in gastrointestinal smooth muscle. The effects of noradrenaline on the pacemaker currents in cultured ICCs from murine small intestine were investigated by using whole-cell patch-clamp techniques at 301C. 2 Under current clamping, ICCs had a mean resting membrane potential of À5875 mV and produced electrical slow waves. Under voltage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…Namely, in ICC, the generation of pacemaker currents and the regulation of ATP-sensitive K + channels on this may involve the cAMP signaling. However, in a recent study and figure 5B, the treatment 8-bromo-cAMP (a cell-permeable cAMP analog) in ICC had no effects on pacemaker currents [48]. Also, pretreatment with SQ-22536, an adenylate cyclase inhibitor, does not influence PGE 2 actions on pacemaker currents, and in a cAMP assay, PGE 2 did not stimulated the production of cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, in ICC, the generation of pacemaker currents and the regulation of ATP-sensitive K + channels on this may involve the cAMP signaling. However, in a recent study and figure 5B, the treatment 8-bromo-cAMP (a cell-permeable cAMP analog) in ICC had no effects on pacemaker currents [48]. Also, pretreatment with SQ-22536, an adenylate cyclase inhibitor, does not influence PGE 2 actions on pacemaker currents, and in a cAMP assay, PGE 2 did not stimulated the production of cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that β-adrenoceptor activation modulates pacemaker activity in cultured mouse intestinal ICC (Jun et al, 2004) suggesting that phentolamine exhibits activity on the pacemaker activity of ICC. We have also observed that phentolamine inhibits ICC pacemaker activity as per our preliminary result.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two studies have addressed the question of whether or not neurotransmitters directly regulate pacemaker currents in ICC. In isolated ICC of the murine small intestine, noradrenaline modulates pacemaker currents by decreasing pacemaker frequency (Jun et al, 2004). In ICC of the murine stomach, acetylcholine increased pacemaker frequency (Kim et al, 2003).…”
mentioning
confidence: 99%